HUBUNGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET Fe DENGAN KEJADIAN ANEMIA DI DESA PAGERAJI KECAMATAN CILONGOK KABUPATEN BANYUMAS - Hidayah, Wiwit; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
Compliance in consumption of iron tablets is obedience of pregnant women health workers carry out the recommendation to consume iron tablets. Supplementation of iron or Fe tablets is one of the important efforts in preventing and combating anemia, especially iron deficiency anemia. To find out the correlation of compliance of pregnant women in consume tablets Fe with the incidence of anemia in the Pageraji Village Cilongok District Banyumas Regency. This research used descriptive correlation study of with case control design and retrospective approach. The study population was all mothers who have been pregnant and given birth who received 90 iron tablets in the Pageraji Village Cilongok District Banyumas Regency period January to December 2010 as many as 127 people. Case and control samples respectively taken as many as 56 people with simple random sampling technique. Methods of data analysis in this study used Chi Square test.CancelIndonesian to English translation Pregnant women who were obedient to consume more iron tablets (50,9%) than the disobidient (49,%). Pregnant women in the Pageraji Village Cilongok District Banyumas who were anemic and anemic same amount that is 56 people (50,0%). There was a correlation between the compliance of pregnant women consume tablets Fe with the incidence of anemia in the Pageraji Village Cilongok District Banyumas Regency with a p value = 0,005. There was a correlation between the compliance of pregnant women consume tablets Fe with the incidence of anemia in the Pageraji Village Cilongok District Banyumas Regency. Keywords                   :  obedience, tablet Fe, anemia